Perancangan Antarmuka Pengguna Aplikasi Mobile Learning pada Mata Pelajaran Komputer dan Jaringan Dasar dengan Metode Human Centered Design (Studi Kasus: Kelas X TKJ di SMKN 1 Dlanggu Mojokerto) - Nurul Fikriyah; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Mobile learning application in Computer and Basic Network subjects is an innovation from the Vocational Hight School 1 Dlanggu school. The purpose of innovation in making this application is an application that is shown in the teaching and learning process. In making or developing applications, an interface design display is needed in the form of a prototype. The design process in the mobile learning application user interface uses the Human Centered Design (HCD) method that focuses on users and user needs. In testing the prototype using the heuristic evaluation method. Heuristic evaluation (HE) to assess and find usability problems based on heuristic principles for e-learning with the help of an expert or expert as an evaluator. After heuristic testing has been carried out, the next step is to carry out tests involving users using the System Usability Scale (SUS) method to produce user satisfaction or satisfaction. The results of the solution design prototype were carried out 2 times of heuristic testing, the first stage found findings of 36 problems and the second stage decreased by 20 problems to 16 problem findings in the evaluation of the solution design. While the results of the system usability scale (SUS) questionnaire get a score of 73, which means that the results of the dolution design prototype can be accepted by the user. The results of this study can be used as design recommendations in the development of mobile learning applications.